GROWTH ANALYSIS OF SOYBEAN UNDER DRY LAND WITH APPLICATION OF Bradyrhizobium japonicum INDUCED BY GENISTEIN AND ORGANIC FERTILIZER (Talenta Publisher, 2015)
This study aimed to get the information of soybean growth response on inoculation of B. japonicum induced genistein under dry land. The experiment was conducted in farmer fields at Desa Sambirejo, Langkat on June-September 2012. The study used a factorial randomized block design with two factors and three replications. The first factor is genistein induction treatment consisting of without and genistein (50 μM). The second factor is the treatment of B. japonicum and organic fertilizer consisted of without B. japonicum; B. japonicum; B. japonicum + manure 10 t/ha; B. japonicum straw compost + 10 t/ha; B. japonicum + manure 5 t/ha + straw compost 5 t /ha. The variables observed are plant growth rate, plant growth relative and net assimilation rate. The results showed that the treatment of genistein (50 μM) decreased the plant growth rate 5-6 WAP, plant growth relative 5-6 WAP and net assimilation rate. Treatment of B. japonicum + manure 5 t/ ha + straw compost 5 t/ ha tent to increase plant growth rate, plant growth relative and net assimilation rate. The interaction between genistein induction and treatment B. japonicum + organic fertilizer tended to decrease plant growth rate, plant growth relative and net assimilation rate.